2023
DOI: 10.1038/s41370-023-00522-4
|View full text |Cite
|
Sign up to set email alerts
|

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies

Abstract: Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Therefore, the dietary habits of children between the ages 5 to 13 were not included. Nevertheless, results by ( Kolbaum, Ptok, Jung, Libuda, & Lindtner, 2023 ) showed that the resource-saving approach of considering only young children and adults in the MEAL study was sufficient to cover the food consumption habits of the middle groups as well. Since the consumption surveys were conducted in 2002 (VELS) and 2006 (NVS II), new foods and consumption trends emerged, which were not included in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the dietary habits of children between the ages 5 to 13 were not included. Nevertheless, results by ( Kolbaum, Ptok, Jung, Libuda, & Lindtner, 2023 ) showed that the resource-saving approach of considering only young children and adults in the MEAL study was sufficient to cover the food consumption habits of the middle groups as well. Since the consumption surveys were conducted in 2002 (VELS) and 2006 (NVS II), new foods and consumption trends emerged, which were not included in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Since the consumption surveys were conducted in 2002 (VELS) and 2006 (NVS II), new foods and consumption trends emerged, which were not included in the present study. As shown by Kolbaum et al (2023) , new foods which may have high AA levels such as chicken nuggets/breaded chicken, veggie schnitzel and marshmallows could be added to the current food list. On the other hand, foods that contained high AA levels in our study such as gingerbread and gingerbread products, and omelette with potatoes and bacon are currently not as relevant as before and could be excluded from a future food list ( Kolbaum et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation